PENGARUH KADAR THIAMINE (VITAMIN B1) TERHADAP PERTUMBUHAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Munir Munir; Fitratul aini; Siti Jariah (Biota, 2016)
Indonesia is one of the centers of biodiversity in particular areas of food, which one of them is from a species of white oyster mushroom (Pleurotus ostreatus). To improve the effectiveness and efficiency of production time associated with fulfilling the request of the oyster mushroom (Pleurotus ostreatus) is high in the market, the utilization of thiamine (vitamin B1) need to be investigated. This study aims to determine the levels of thiamine (vitamin B1), which is best used in the growth of oyster mushroom (Pleurotus ostreatus). This study used quantitative experiments and research design complete randomized design with four treatments and six times as many repetitions as well as research along with the observations made on 21 June to 11 July 2015 (in 20 days) in the House of White Oyster Mushroom Production Nurseries, Ogan Komering Ulu Timur (OKUT). As for the levels of thiamine (vitamin B1) used in this study use the unit ppm (parts per million), namely: B0 (control), B1 (0.1 ppm), B2 (0.2 ppm), B3 (0.3 ppm). Parameters measured were the growth of oyster mushroom (Pleurotus ostreatus) which include emerging buds time (day), the time of harvest (days), weight (grams), wide hood (cm), and stem length (cm). Conclusions from the study and based on data analysis (ANOVA) and F test showed that administration of thiamine (vitamin B1) does not provide an effective influence on the growth of oyster mushroom (Pleurotus ostreatus).